On contact interactions as limits of short-range potentials - Bräunlich, G.; Haizl, C.; Seiringer, R. (Methods of Functional Analysis and Topology, 2013)
We reconsider the norm resolvent limit of -Δ + V_ with V_ tending to a point interaction in three dimensions. We are mainly interested in potentials V_ modelling short range interactions of cold atomic gases. In order to ensure stability the interaction V_ is required to have a strong repulsive core, such that _→ 0 V_>0. This situation is not covered in the previous literature.